2019
DOI: 10.1136/svn-2019-000262
|View full text |Cite
|
Sign up to set email alerts
|

Acute ischaemic stroke interventions: large vessel occlusion and beyond

Abstract: Care for acute ischaemic stroke is one of the most rapidly evolving fields due to the robust outcomes achieved by mechanical thrombectomy. Large vessel occlusion (LVO) accounts for up to 38% of acute ischaemic stroke and comes with devastating outcomes for patients, families and society in the pre-intervention era. A paradigm shift and a breakthrough brought mechanical thrombectomy back into the spotlight for acute ischaemic stroke; this was because five randomised controlled trials from several countries conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 75 publications
0
20
0
1
Order By: Relevance
“…This disorder carries a high morbidity and mortality rate as well as long-term psychosocial, economic, and physical repercussions, with a devastating impact on the quality of life of patients and their caregivers [2]. Large vessel occlusion (LVO) stroke occurs due to acute blockages of the proximal cerebral circulation and accounts for approximately 24%-46% of AIS, with two-thirds of LVO occurring in the anterior circulation [3,4]. Multiple recent randomized controlled trials [5][6][7][8][9] have demonstrated the efficacy of endovascular thrombectomy (EVT), cementing the role of EVT as the standard of care for AIS with proximal LVO in the anterior circulation [10].…”
Section: Introductionmentioning
confidence: 99%
“…This disorder carries a high morbidity and mortality rate as well as long-term psychosocial, economic, and physical repercussions, with a devastating impact on the quality of life of patients and their caregivers [2]. Large vessel occlusion (LVO) stroke occurs due to acute blockages of the proximal cerebral circulation and accounts for approximately 24%-46% of AIS, with two-thirds of LVO occurring in the anterior circulation [3,4]. Multiple recent randomized controlled trials [5][6][7][8][9] have demonstrated the efficacy of endovascular thrombectomy (EVT), cementing the role of EVT as the standard of care for AIS with proximal LVO in the anterior circulation [10].…”
Section: Introductionmentioning
confidence: 99%
“…52 Additionally, every 30min delay in EVT decreases favourable outcomes by 11%. 51 Thus, systems which automatically and promptly detect LVO have the potential to improve EVT rates and expedite treatment.…”
Section: Detection Of Large Vessel Occlusionmentioning
confidence: 99%
“…Hypoxia and hypoglycemia start the ischemic cascade that leads to acute cell death (necrosis) and delayed programmed cell death (apoptosis). Despite the use of acute therapeutic interventions aimed at rapid reperfusion of tissue surrounding the ischemic core, various types of deficits originating from stroke necessitate long-term rehabilitation processes [ 3 , 4 , 5 ]. Of note, hematologic disorders such as coagulopathies and hematologic cell disorders are a commonly unrecognized cause of ischemic stroke in humans, necessitating different treatment approaches according to the particular underlying disorder [ 6 ].…”
Section: Introductionmentioning
confidence: 99%